2007
DOI: 10.1210/jc.2007-0774
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Adrenal Axis Activity in Obese Men with and without Sleep Apnea: Effects of Continuous Positive Airway Pressure Therapy

Abstract: Nonpsychologically distressed, normally sleeping, obese men had low cortisol secretion. The cortisol secretion was slightly activated by SA and returned to low by CPAP use. The low cortisol secretion in obesity through its inferred hyposecretion of hypothalamic CRH might predispose the obese to sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
116
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 38 publications
12
116
1
6
Order By: Relevance
“…The same study also demonstrated that the cortisol increases to Cortrosyn or insulin were similar in the obese and controls. Administration of CRH to obese men with or without sleep apnea syndrome resulted in amplified ACTH release compared with lean controls, but cortisol secretion was not greater (32). Finally, insulin-induced hypoglycemia caused a larger ACTH increase in obese subjects than that in controls, both in the morning and evening, but the cortisol response in obese subjects was diminished in obesity (33).…”
Section: Discussionmentioning
confidence: 83%
“…The same study also demonstrated that the cortisol increases to Cortrosyn or insulin were similar in the obese and controls. Administration of CRH to obese men with or without sleep apnea syndrome resulted in amplified ACTH release compared with lean controls, but cortisol secretion was not greater (32). Finally, insulin-induced hypoglycemia caused a larger ACTH increase in obese subjects than that in controls, both in the morning and evening, but the cortisol response in obese subjects was diminished in obesity (33).…”
Section: Discussionmentioning
confidence: 83%
“…The previous reports including Carneiro's study were that the effect of CPAP therapy for the HPA axis in OSAS patients was examined three months after CPAP therapy [11,[21][22][23]. On the other hand we performed 0.5 mg DST for them within a few but not with AHI (p=0.784), BMI (p=0.984), waist circumference (p=0.967), HbA1c (p=0.261), fasting plasma glucose (p=0.420) or HOMA-IR (p=0.500).…”
Section: Discussionmentioning
confidence: 99%
“…The associated hypoxaemia and the concomitant increase in arterial carbon dioxide tension are expected to result in sympathetic activation and catecholamine secretion, while the repeated arousals can cause activation of the hypothalamic-pituitary-adrenal (HPA) axis, thus increasing cortisol release [2]. However, and contrary to what was expected, most studies have reported no significant association [3][4][5][6][7][8] or decreased HPA axis activity [9], whereas only two studies reported increased HPA axis activity in sleep apnoea patients compared with controls [10,11]. A more recent study [12] found a significant association between apnoea severity and 24-h cortisol values; however, it was limited by the absence of a control group.…”
Section: Introductionmentioning
confidence: 96%
“…Obesity is the strongest risk factor for sleep apnoea, but also a known HPA axis modulator, and thus a possible confounder of the association between sleep apnoea and HPA axis activity [11].…”
Section: Introductionmentioning
confidence: 99%